Phylogeny and phenotypes of clinical and environmental Shiga toxin‐producing Escherichia coli O174. (27th August 2013) - Zhang, Wenlan; Nadirk, Julia; Kossow, Annelene; Bielaszewska, Martina; Leopold, Shana R.; Witten, Anika; Fruth, Angelika; Karch, Helge; Ammon, Andrea; Mellmann, Alexander
Summary Shiga toxin (Stx)‐producing Escherichia coli (STEC) of serogroup O174 are human pathogenic intimin gene (eae)‐negative STEC. To facilitate diagnosis and subtyping, we genotypically and phenotypically characterized 25 STEC O174 isolates from humans with different clinical outcomes and from animals and the environment. fliC genotyping resulted in four different genotypes (fliCH2: n = 5; fliCH8: n = 8; fliCH21: n = 11; fliCH46: n = 1). Twenty‐three strains were motile expressing the corresponding H antigen; two non‐motile isolates possessed fliCH8. The stx genotypes and non‐stx virulence loci, including toxins, serine‐proteases and adhesins correlated well with serotypes but showed no differences with respect to the isolates' origins. Multilocus sequence typing identified seven sequence types that correlated with serotypes. Core gene typing further specified the four serotypes, including a previously unknown O174:H46 combination, and revealed distant relationships of the different serotypes within serogroup O174 and in relation to other haemolytic uremic syndrome (HUS)‐associated STEC. Only serotype O174:H21 was associated with HUS. Differences in virulence factors and in the adherence capacity of STEC O174 corroborated this separation into four distinct groups. Our study provides a basis for O174 subtyping, unravels considerable genotypic and phenotypic heterogeneity and sheds light to potential environmental and animal reservoirs.